EFFECT OF VARIOUS EXTRACTION SYSTEMS ON THE ANTIOXIDANT ACTIVITY KINETIC AND COLOR OF EXTRACTS FROM PURPLE CORN - RAMOS-ESCUDERO, Fernando; GONZÁLEZ-MIRET, María L.; GARCÍA-ASUERO, Agustín (Vitae, 2012)
The purpose of this study was to investigate the effect of extraction systems on the anthocyanin index, antioxidant kinetics (DPPH-radical scavenging capacity) and color of purple corn (Zea mays) seeds. The factors studied were: extraction system (methanol, 100%, 80%, 60%, 40, 20% v/v) using hydrochloric acid as a means of acidifying. Tristimulus colorimetry was applied to evaluate quantitatively and qualitatively the process. The estimated effect and ANOVA parameters were calculated. The anthocyanins index in different extraction systems was between 1.09 to 2.87 mg/g. The highest anthocyanin index was obtained at an extraction system of 100% methanol. To determine their radical scavenging capacity, the second-order rate constant for the oxidation of these extraction systems measured by the DPPH (1,1-diphenyl-2-picrylhydrazyl radical) method, ranged from 1.19x10-2 to 1.27x10-2 (mg/mL)-1(s-1). The greatest second-order rate constant was obtained at an extraction system of 60% methanol. Regarding the simple regressions analysis the anthocyanin index showed a better relationship with CIELAB parameters: (L*; r =-0.928, p < 0.05), (a*; r = 0.982, p < 0.01), (b*; r = 0.927, p < 0.05), (C*ab; r = 0.9793, p < 0.01) and (hab; r = -0.936, p < 0.05). However, the correlation existing between color parameters and the second-order rate constant did not show a good relationship. When multiple linear regression analysis were applied considering the angular coordinates (L*, C*ab, hab) as independent variable values, a R2 nearing 1 was obtained for anthocyanins index. While a value of R2 = 0.63 was obtained for the second-order rate constant.